Breaking Patriarchal Culture in Damsel (2024) Movie: A Semiotic Analysis using John Fiske's Theory - Almasyah Salsabiila; Tuty Handayani; Saefudin; Sholikatus Sadiyah (Prodi Sastra Inggris, Universitas Muhammadiyah Semarang, 2025)
This research aims to analyse how the Damsel (2024) movie breaks down patriarchal culture. It used John Fiske's semiotic theory, which focuses on three levels: reality, representation, and ideology. The method of this research is qualitative methods and used data card techniques as a tool to obtain valid data. By taken from scenes and dialogue in the Damsel (2024) movie which contained depictions of patriarchal culture and efforts to break it from beginning to end, resulted. The results of this research is to show how patriarchal culture is represented in Elodie's family and environment, and her responses including the arranged marriage by her parents. The ideology presented here is feminism ideology through John Fiske's theory. Elodie's character successfully breaks through the existing patriarchal culture and demonstrates feminism ideology and supported John Fiske’s theory. The movie served as a medium for feminism and the defense of women’s rights in both fictional narratives and broader societal contexts.